New flow control systems in capillarics: off valves. Issue 1 (9th December 2020) - Menges, Julian; Meffan, Claude; Dolamore, Fabian; Fee, Conan; Dobson, Renwick; Nock, Volker
Abstract : Off-valves, fabricated by a simple milling process and engaged by trigger channels, enable autonomous flow and sequencing control in capillary circuits for point-of-care applications. Abstract : Capillary systems are a promising technology for point-of-care microfluidics, since they are pre-programmable and self-powered. This work introduces "off valves" as a key building block for capillaric circuits, providing easy-to-use, multi-purpose valving functionality and autonomous flow control. To this end we present a set of switching valve designs that use trigger channels and liquid input alone to close or open connections between channels in a highly controllable fashion. The key element of all these valve designs is a new off trigger valve, which is characterised in detail here and holds the potential for transistor-like switching and resistance tuning. As an example for the potential applications of switching valves, we demonstrate how they can be used for flow resistance control in a complex microfluidic circuit and for sequential chemical loading into a reaction chamber. Use of the switching valves for the latter in particular allowed for the tuning of incubation times and volumetric measurement, thus confirming applicability of the valves for automated and self-powered immunoassays in point-of-care environments.